1973
DOI: 10.1126/science.182.4113.715
|View full text |Cite
|
Sign up to set email alerts
|

Grazing by the Echinoid Diadema antillarum Philippi: Formation of Halos around West Indian Patch Reefs

Abstract: Between patch reefs and marine grass communities there is normally a zone or "halo" of heavily grazed grass 2 to 10 meters wide. Grazing by the echinoid Diadema antillarum Philippi during nocturnal migrations off the reefs is found to be the major factor in the formation of halos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
189
2
3

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(207 citation statements)
references
References 4 publications
13
189
2
3
Order By: Relevance
“…Herbivorous fishes are the main group of grazers in the new situation, and the change in cover indicates that competition for food occurred between fishes and urchins in pre-mortality conditions. This is supported by observations that, after experimental removal of D. antillarum, the number of herbivorous fishes as well as their activity increased (Ogden et al 1973, Hay & Taylor 1985. Momson (1984) and Carpenter (1985) also reported an increase of grazing activities by herbivorous fishes in shallow reefs following D. antillarum mortalities at Jamaica and St. Croix, respectively.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Herbivorous fishes are the main group of grazers in the new situation, and the change in cover indicates that competition for food occurred between fishes and urchins in pre-mortality conditions. This is supported by observations that, after experimental removal of D. antillarum, the number of herbivorous fishes as well as their activity increased (Ogden et al 1973, Hay & Taylor 1985. Momson (1984) and Carpenter (1985) also reported an increase of grazing activities by herbivorous fishes in shallow reefs following D. antillarum mortalities at Jamaica and St. Croix, respectively.…”
Section: Discussionsupporting
confidence: 71%
“…Grazing organisms are found among molluscs and small crustaceans (Brawley & Adey 1981) but fishes and sea urchins are the main groups of herbivores, though their relative importance varies with characteristics of the reef habitat (Randall 1965, Ogden et al 1973, Ogden & Lobel 1978, Hay 1984. Competition for space on the Limited hard substratum occurs between an array of organisms and is a possible structuring force on many reefs (Jackson & Buss 1975, Jackson 1977, Karlson 1980, Benayahu & Loya 1981, Bak et al 1982, Bak & Borsboom 1984.…”
Section: Introductionmentioning
confidence: 99%
“…Keen & Neill 1980, Russ 1980, Chalmer 1982, however organisms can respond differentially to patches of habitat and thereby may exert potentially important 'edge effects'. Edge effects can result from patterns in the settlement of organisms (Bernstein & Jung 1979, Schoener & Schoener 1981, this study), and they have been shown to arise through the action of grazers in a number of systems (Randall 1965, Bartholomew 1970, Dayton 1971, Ogden et al 1973, Stimson 1973, Suchanek 1978, Paine & Levin 1981, Sousa 1984.…”
Section: Edge Effectsmentioning
confidence: 81%
“…Many studies have focused on the effects of grazing by D. antillarum on coral reef communities (Ogden et al, 1973;Sammarco, 1980Sammarco, , 1982Carpenter, 1981Carpenter, , 1984Carpenter, , 1986Carpenter, , 1997Hay, 1984;Foster, 1987;Hughes, Keller, Jackson & Boyle, 1987;Hughes, 1989;Williams & Carpenter, 1997;Edmunds & Carpenter, 2001;Williams & Polunin, 2001;Carpenter & Edmunds, 2006;Furman & Heck, 2009). The direct effects of grazing by D. antillarum are: (1) reduction of algal biomass, (2) enhancement of primary productivity rates on algal turf communities, (3) shifts of algal community composition and diversity, and (4) mortality of recruits and small juveniles of sessile marine invertebrates (Ogden et al, 1973;Sammarco, 1980;Carpenter, 1981Carpenter, , 1984Carpenter, , 1986Carpenter, , 1997Foster, 1987;Hughes et al, 1987;Hughes, 1989Williams & Carpenter, 1997Williams & Polunin, 2001;Edmunds & Carpenter, 2001;Carpenter & Edmunds, 2006).…”
Section: Grazing By D Antillarum and Coral Recruitmentmentioning
confidence: 99%